2020
DOI: 10.3389/fpls.2020.00072
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Seed-Applied Biofertilizers on Rhizosphere Biodiversity and Growth of Common Wheat (Triticum aestivum L.) in the Field

Abstract: In order to reduce chemical fertilization and improve the sustainability of common wheat (Triticum aestivum L.) cultivation, maintaining at the same time high production and quality standards, this study investigated the effects of three commercial biofertilizers on rhizosphere bacterial biomass, biodiversity and enzymatic activity, and on plant growth and grain yield in a field trial. The wheat seeds were inoculated with the following aiding microrganisms: (i) a bacterial consortium (Azospirillum spp. + Azoar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(59 citation statements)
references
References 67 publications
5
53
0
1
Order By: Relevance
“…Rhizosum PK ® is a biofertilizer containing i.a. Bacillus megaterium and Frateuria aurantia which were found to exhibit potassium-mobilizing properties [49][50][51]. A study conducted by Mengual et al [52] showed that the introduction of microbial inoculants to the soil positively the affected activities of urease, protease and β-glucosidase with significant changes occurring in the case of urease and protease.…”
Section: Discussionmentioning
confidence: 99%
“…Rhizosum PK ® is a biofertilizer containing i.a. Bacillus megaterium and Frateuria aurantia which were found to exhibit potassium-mobilizing properties [49][50][51]. A study conducted by Mengual et al [52] showed that the introduction of microbial inoculants to the soil positively the affected activities of urease, protease and β-glucosidase with significant changes occurring in the case of urease and protease.…”
Section: Discussionmentioning
confidence: 99%
“…However, several biotic and abiotic factors may impact on the ability of plant-aiding microorganisms to successfully colonize the rhizosphere. Therefore, PGPM should tolerate nutrient- or water-limited conditions, be affine for root exudates, and compete with the resident rhizobacteria by secreting antibiotics [ 76 ]. For instance, [ 74 , 115 ] investigated the action of plant-derived protein hydrolysates (PHs) biostimulant and the effects of the mycorrhizal inoculation on morpho-physiological traits and metabolic profile of tomato and durum wheat respectively, grown under limited water availability.…”
Section: Targeted and Untargeted Approaches To Soil Microbial Diversity Managementmentioning
confidence: 99%
“…Recent studies have investigated the effects on the rhizosphere microbial communities of different types of microbial consortia (consisting of PGPRs alone or in association with AMFs) and biostimulant substances coated on crop seeds. All microbial consortia and biostimulant substances significantly enhance plant growth and nitrogen accumulation in wheat and maize, without affecting the endogenous microbial diversity or the composition of the rhizospheric microbial community, rather stimulating rare bacterial taxa, some of which involved in plant growth and pathogen resistance [ 61 , 76 , 81 ]. This suggests that seed-applied biofertilizers may be exploited effectively in sustainable cultivation.…”
Section: Targeted and Untargeted Approaches To Soil Microbial Diversity Managementmentioning
confidence: 99%
See 2 more Smart Citations